2020
DOI: 10.1111/bph.15022
|View full text |Cite
|
Sign up to set email alerts
|

The antiarrhythmic compound efsevin directly modulates voltage‐dependent anion channel 2 by binding to its inner wall and enhancing mitochondrial Ca2+ uptake

Abstract: Background and Purpose: The synthetic compound efsevin was recently identified to suppress arrhythmogenesis in models of cardiac arrhythmia, making it a promising candidate for antiarrhythmic therapy. Its activity was shown to be dependent on the voltage-dependent anion channel 2 (VDAC2) in the outer mitochondrial membrane.Here, we investigated the molecular mechanism of the efsevin-VDAC2 interaction.Experimental Approach: To evaluate the functional interaction of efsevin and VDAC2, we measured currents throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 44 publications
0
29
0
2
Order By: Relevance
“…Authors concluded that this mechanism could explain the efsevin-induced facilitated transfer of calcium from the sarcoplasmic reticulum into mitochondria in zebra fish. Interestingly, in these studies, efsevin has not been observed to be involved in apoptosis (Schweitzer et al, 2017;Wilting et al, 2020) despite the accepted role of VDAC2 in apoptosis through recruitment of Bax or Bak (Cheng et al, 2003;Chin et al, 2018).…”
Section: Screening Non-polar Compounds For Vdac Functional Controlmentioning
confidence: 89%
See 2 more Smart Citations
“…Authors concluded that this mechanism could explain the efsevin-induced facilitated transfer of calcium from the sarcoplasmic reticulum into mitochondria in zebra fish. Interestingly, in these studies, efsevin has not been observed to be involved in apoptosis (Schweitzer et al, 2017;Wilting et al, 2020) despite the accepted role of VDAC2 in apoptosis through recruitment of Bax or Bak (Cheng et al, 2003;Chin et al, 2018).…”
Section: Screening Non-polar Compounds For Vdac Functional Controlmentioning
confidence: 89%
“…Efsevin is thought to enhance mitochondrial uptake of calcium through VDAC2, thereby preventing calcium accumulation in the cytosol (Schweitzer et al, 2017). Lately, using an in vitro system of reconstituted zfVDAC2 channels, Wilting et al (2020) found that efsevin promotes channel closure and shifts its selectivity toward less anionic thus, according to the previous studies (Rostovtseva et al, 2005;Tan and Colombini, 2007), ultimately causing an increase of VDAC2 permeability for calcium. Authors concluded that this mechanism could explain the efsevin-induced facilitated transfer of calcium from the sarcoplasmic reticulum into mitochondria in zebra fish.…”
Section: Screening Non-polar Compounds For Vdac Functional Controlmentioning
confidence: 95%
See 1 more Smart Citation
“…VDAC2 образован бочкообразной структурой, состоящей из 19 антипараллельных β-листов и N-концевой α-спирали, выстилающей внутреннюю стенку канала [25]. Сайт связывания с эфсевином расположен в так называемой канавке между внутренней стенкой канала и α-спиралью [26]. VDAC подвергается зависящему от напряжения стробированию между анион-селективным состоянием высокой проводимости, называемым классическим открытым состоянием, и несколькими катион-селективными состояниями низкой проводимости, именуемыми закрытыми состо-яниями [27,28], т. е. закрытые состояния VDAC более катион-селективные по сравнению с открытым состоянием [29].…”
Section: Vdac2 -мишень для действия эфсевинаunclassified
“…Кроме того, связывание эфсевина с другими мишенями, включая изоформы VDAC1 и VDAC3, никогда не тестировалось. Таким образом, его неизвестная селектив-ность, низкая стабильность эфсевина указывают на необходимость химической оптимизации соединения перед проведением дальнейших доклинических и клинических исследований [26].…”
Section: побочные эффекты эфсевина и его фармакокинетикаunclassified